Comparative Analysis of Residents' Self-Assessment of Health in the City of Makhachkala and the Untsukulskiy District of the Republic of Dagestan - P. A. Bekshokova; K. K. Bekshokov; A. R. Ibragimova; A. A. Ramazanova; G. M. Mukhtarova (Юг России: экология, развитие)
Aim. To conduct a comparative analysis of the self-assessment of health by urban and rural residents of the Republic of Dagestan, using as examples the city of Makhachkala and the Untsukulskiy district.Material and Methods. Sociological research methods were employed on the basis of questionnaires.Results. According to the results of the study the majority of the residents of Makhachkala and the Untsukulskiy district surveyed - 71% and 68.2% respectively -gave positive assessments of their health. In both samples, the proportion of respondents who rated their health as "mediocre" and "bad" increased with age. In rural areas the number of young and middle-aged respondents who assessed their health as worse exceeded the number of city dwellers of the same age. Among male respondents, 77.8% in Makhachkala and 74.9% in the Untsukulskiy district gave a positive self-assessment of health and among the female population, 66.7% and 62.93% respectively.Conclusion. Self-assessment of health is a tool recommended by the World Health Organization for monitoring health within selected population groups. The slight difference between the assessment of their health by urban and rural residents is due to differences in lifestyle and standard of living, access to medical as well as cultural, leisure and other types of services.